PENERAPAN METODE PENEMUAN TERBIMBING PADA MATERI LUAS PERMUKAAN DAN VOLUME BOLA DI KELAS IX - Widiawati, Widiawati; Rahayu, Chika; Widyaningrum, Indah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The purpose of this research is to know how the student activity during the applied method of guided discovery and student learning outcomes after applied guided discovery method on the material surface area and volumeof sphere in class IX. The method used in this study is the method of quasi-experimental category one short case study, in which the sample taken one class of 37 people conducted in SMP Negeri 3 Pagaralam. Technique of collecting data with observation and test method. To find out student activity used observation sheet, then look for percentage of overall activity. Meanwhile, to find the average value used the average calculation formula (mean). From the data analysis, obtained the average percentage of total student activity during applied guided discovery method is good. Likewise with student learning outcomes after applied guided discovery methods are also categorized well. Thus, guided discovery methods are very well used especially in mathematics learning. Keywords: Guided Discovery Method, Learning Activity, Learning Outcomes.